2008
DOI: 10.1371/journal.ppat.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Unfolded Protein Response Is Required for Defenses against Bacterial Pore-Forming Toxin In Vivo

Abstract: Pore-forming toxins (PFTs) constitute the single largest class of proteinaceous bacterial virulence factors and are made by many of the most important bacterial pathogens. Host responses to these toxins are complex and poorly understood. We find that the endoplasmic reticulum unfolded protein response (UPR) is activated upon exposure to PFTs both in Caenorhabditis elegans and in mammalian cells. Activation of the UPR is protective in vivo against PFTs since animals that lack either the ire-1-xbp-1 or the atf-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
219
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(232 citation statements)
references
References 43 publications
9
219
3
1
Order By: Relevance
“…Endoplasmic reticulum (ER) stress pathways are central for host survival against PFTs, including LLO, and ER distribution is often altered during intoxication [10,11]. Concurrently, we have shown that Lm infection redistributes the ER chaperone Gp96 to the PM through an uncharacterized mechanism [12].…”
Section: Introductionmentioning
confidence: 83%
“…Endoplasmic reticulum (ER) stress pathways are central for host survival against PFTs, including LLO, and ER distribution is often altered during intoxication [10,11]. Concurrently, we have shown that Lm infection redistributes the ER chaperone Gp96 to the PM through an uncharacterized mechanism [12].…”
Section: Introductionmentioning
confidence: 83%
“…the cell membrane such as that caused by a poreforming toxin, which activates the unfolded protein response downstream of PMK-1 (Bischof et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limit, a new collision-activated fragmentation technique, called PQD, was invented that enables routine and reliable measurement of ions down to 50 m/z (18). We have developed and successfully applied a combined CID-PQD scan approach for peptide identification and quantitation (19,20).…”
Section: Fig 1 Overview Of Experimental Design and Sample Collectionmentioning
confidence: 99%